The Role of Labor Market Intermittency in Explaining Gender Wage Differentials - Hotchkiss, Julie L; Pitts, M. Melinda (American Economic Review, 2007)
The Role of Labor Market Intermittency in Explaining Gender Wage Differentials by Julie L. Hotchkiss and M. Melinda Pitts. Published in volume 97, issue 2, pages 417-421 of American Economic Review, May 2007